Pengaruh Model Pembelajaran Team Games Tournament Terhadap Hasil Belajar Siswa - Fauziah, Desi; Kurjono, Kurjono; Muntasofi, Badria (Universitas Pendidikan Indonesia, 2018)
Abstract. The problem examined in this study is the still low student learning outcomes in accounting subjects. The purpose of this study was to differentiate student learning outcomes in the class applying the Team Games Tournament learning model with classes that did not apply the Team Games Tournament learning model. The research method used is the quasi-experimental method with the Post Test Control Group Design Pre Test design. The population in this researcher is all students of class XI IPS SMAN 1 Kawali 2016/2016 academic year which consists of 5 classes with a total of 154 students. While the sample used was students of class XI IPS 4 as an experimental class and students of class XI IPS 5 as a control class with a purposive sampling technique. The data collection tool for student learning outcomes is obtained by giving tests in the form of description questions. The data analysis technique uses the normality test, homogeneity test and for hypothesis testing using the t test. Hypothesis test results obtained that the value of t_count> t_table is t_count = 2.3484> t_table = 2.002 then Ho is rejected and H1 is accepted. This means that there are differences in learning outcomes between students using the Team Games Tournament learning model, and students who do not use the Team Games Tournament learning model. The average post test results of students in the experimental class were 87.12 while the average post-test results of students in the control class was 80.7. This is the basis for researchers to argue that the application of the Team Games Tournament learning model influences student learning outcomes Keywords. learning outcomes; cooperative learning model; team games tournament type Abstrak.Masalah yang dikaji dalam penelitian ini adalah masih rendahnya hasil belajar siswa pada mata pelajaran akuntansi. Tujuan penelitian ini adalah untuk perbedaan hasil belajar siswa pada kelas yang menerapkan model pembelajaran Team Games Tournament dengan kelas yang tidak menerapkan model pembelajaran Team Games Tournament. Metode penelitian yang digunakan adalah metode kuasi eksperimen dengan bentuk desain Pre Test Post Test Control Group Design. Populasi dalam peneliti ini adalah seluruh siswa kelas XI IPS SMAN 1 Kawali tahun ajaran 2016/2017 yang terdiri dari 5 kelas dengan jumlah 154 siswa. Sedangkan sampel yang digunakan adalah siswa kelas XI IPS 4 sebagai kelas eksperimen dan siswa kelas XI IPS 5 sebagai kelas kontrol dengan teknik pengambilan sampel purposive sample. Alat pengumpulan data untuk hasil belajar siswa diperoleh dengan memberikan tes dalam bentuk soal uraian. Teknik analisis data menggunakan uji normalitas, uji homogenitas dan untuk pengujian hipotesis menggunakan uji t. Hasil uji hipotesis diperoleh bahwa nilai > yaitu = 2,3484 > 2,002 maka Ho ditolak dan H1 diterima. Artinya, bahwa terdapat perbedaan hasil belajar antara siswa yang mengguanakan model pembelajaran Team Games Tournament ,dengan siswa yang tidak menggunakan model pembelajaran Team Games Tournament. Rata-rata hasil post test siswa pada kelas eksperimen adalah 87,12 sedangkan rata-rata hasil post test siswa pada kelas kontrol adalah 80,7. Hal tersebut menjadi dasar bagi peneliti untuk berpendapat bahwa penerapan model pembelajaran Team Games Tournament berpengaruh terhadap hasil belajar siswa Kata Kunci. hasil belajar; model pembelajaran kooperatif; tipe team games tournament